R&D projects co-financed by public funds - Jerónimo, C. H.; Barroso, D.; Pereira, L.; Lopes da Costa, R.; Dias, Á.; Gonçalves, R. (International Journal of Procurement Management, 2023)
Governments develop public policies such as collaborative programs through direct funding to execute projects that impact economic competitiveness. This impact will only be felt if the execution of the projects is successful. This research has the purpose of evaluating the efficiency of I&D projects co-financed by public funds in Portugal through the application of project management practices. Interviews were conducted with companies' beneficiary of public financing in collaborative I&D projects and the entities responsible for the monitoring of the projects. It was found that, in Portugal, companies that execute co-funded collaborative R&D projects lack rigor when applying project management methodologies and that there also exists a need to adapt legislation regarding the application of project management practices to projects in the area.